Regularity results for a quasilinear free boundary problem - Challal, Samia; Lyaghfouri, Abdeslem (Mathematical Modelling and Analysis, 2020)
In this paper we prove local interior and boundary Lipschitz continuity of the solutions of a quasilinear free boundary problem. We also show that the free boundary is the union of graphs of lower semi-continuous functions.